The Hormonal dysregulation and its consequences in Obese Women - overview - Pala, Katarzyna Maria; Tomaszewska, Wiktoria; Siudziński, Paweł; Łyko, Mateusz; Skoczylas, Alicja; Golińska, Maria; Nowak, Anna; Kurasz, Jakub; Podlasiewicz, Wiktoria; Dudziak, Piotr; Maj, Wojciech (Journal of Education, Health and Sport, 2025)
Introduction Obesity, a global health challenge, significantly impacts women's hormonal balance, affecting metabolic and reproductive health. Defined as a BMI >30 kg/m² by WHO, its prevalence is rising, creating substantial health and economic challenges. Aim of Study This study explores the effects of obesity on women's hormonal regulation, emphasizing associated conditions like PCOS, insulin resistance, infertility, and cardiometabolic diseases, while identifying mechanisms and potential interventions. Material and Methods A review of 34 peer-reviewed articles (2000–2024) using PRISMA criteria analyzed hormonal imbalances caused by obesity, focusing on adipokines such as leptin and adiponectin, and their roles in glucose metabolism, lipid regulation, and inflammation. Analysis of Literature Obesity-induced chronic inflammation disrupts insulin regulation, sex hormones, and the hypothalamic-pituitary-adrenal axis. It causes ovulatory disorders, reduced oocyte quality, and impaired endometrial receptivity. Mechanisms like insulin resistance, hyperandrogenism, and leptin dysfunction are central to these effects. Conclusion A multidimensional treatment approach, including lifestyle changes, pharmacotherapy (e.g., GLP-1 agonists), and surgical interventions, is essential. Personalized strategies can alleviate symptoms, improve metabolic and reproductive outcomes, and enhance quality of life for women with obesity.